2021
DOI: 10.1021/acs.jpcb.1c04504
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of C–F···H–C Attractive Interaction: Enforced Coplanarity of a Tetrafluorophenylene-Ethynylene-Linked Porphyrin Dimer

Abstract: The formation of C–F···H–C “hydrogen bonds” has been a controversial subject because, in principle, fluorine is hardly an acceptor for less acidic protons contrasting to the C–F···H–O and C–F···H–N hydrogen bonds. Nevertheless, the interaction is emerging as a powerful implement for confining the torsional rotation in the design of fully coplanar π-conjugated polymers. Heretofore, no evidence of the C–F···H–C interaction has been observed in solutions. We herein disclose comprehensive evidence that the C–F···H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 86 publications
0
22
0
Order By: Relevance
“…Then, the formidable purification using size-exclusion chromatography (SEC) is required to ensure the purity of 1 π satisfactory to photophysical investigations. , Therefore, the improved synthetic protocols of the Sonogashira cross-coupling reaction will open a new avenue to develop porphyrin-based materials. In our preceding study, we found that dichloromethane (DCM) is an effective solvent to minimize the Glaser homocoupling in Route B1 for the synthesis of 1 π in some cases. , This study extends the scope of the solvent-modulated approach (Route B1 ). Furthermore, we refined the Shultz’s approach and eventually developed a novel alternative methodology: the trimethylsilanolate-promoted Hiyama-type Sonogashira approach using potassium trimethylsilanolate (KOTMS) (Route B4 ).…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…Then, the formidable purification using size-exclusion chromatography (SEC) is required to ensure the purity of 1 π satisfactory to photophysical investigations. , Therefore, the improved synthetic protocols of the Sonogashira cross-coupling reaction will open a new avenue to develop porphyrin-based materials. In our preceding study, we found that dichloromethane (DCM) is an effective solvent to minimize the Glaser homocoupling in Route B1 for the synthesis of 1 π in some cases. , This study extends the scope of the solvent-modulated approach (Route B1 ). Furthermore, we refined the Shultz’s approach and eventually developed a novel alternative methodology: the trimethylsilanolate-promoted Hiyama-type Sonogashira approach using potassium trimethylsilanolate (KOTMS) (Route B4 ).…”
Section: Introductionmentioning
confidence: 54%
“…At the first stage, we reconsider our strategy to achieve the exclusive Sonogashira cross-coupling conditions, the so-called solvent-modulated approach (Route B1 , Scheme ). The conditions also improved the isolated yield of 1 C6F4 (59%) . Herein, we extend the scope of the solvent-modulated strategy.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Stronger intramolecular hydrogen bonds (H-bonds) have also been used to lock the conformation of π-conjugated molecular systems. For the typical C–H···F, , C–H···O, , N–H···O, , and N–H···N interactions, the H-bond-induced stabilizations of coplanar conformations are in the range of 7–14 kcal/mol. Many literature examples exhibited intriguing properties induced by the coplanar conformation, such as anisotropic molecular aggregation, solvent resistance, and increased charge carrier mobility. ,,, Despite the potential of the H-bond approach, efficient synthetic strategies to incorporate robust intramolecular H-bonds into conjugated π-systems are still relatively limited.…”
mentioning
confidence: 99%